Collaboration in the Malaysian construction industry: Investigating what, why and how - Lim, Sin Ying (2021)
In a climate of stiff competition, poor collaboration has been identified as the leading root cause of poor project performance. Now more than ever, construction actors are called to draw more attention to the collaboration issues, for a number of reasons. Despite the collaboration working concept gaining growing recognition in the global construction industry, it is still in an infancy level in the Malaysian construction sector, and its value is still being questioned. It is therefore essential to examine the collaboration issues within Malaysian construction practitioners. Specifically, this study aims to recognise the importance of collaboration, identify the common barriers leading to poor collaboration and explore potential strategies for addressing all the associated impediments. This was done by first identifying the research problems and objectives through reviewing of existing literature, followed by a systematic quantitative data collection via questionnaire surveys. A total of 151 responded questionnaires were collected from different groups of Malaysian construction practitioners (clients, consultants and contractors). The data collected were then subjected to reliability analysis, descriptive statistics, and inferential statistics. Based on the findings, “better quality control”, “better time control”, and “effective problem solving” were found to be the significant motivational factors affecting collaboration decisions. Also, “resistant to change current way of working”, “communication problem” and “incompatible personalities and organisational cultures” have been recognised as the top three barriers that impede collaboration. Nevertheless, the findings also revealed that “effective communication”, “mutual objectives”, “trust building”, “performance measurement” and “effective problem resolution” as the best means to promote collaboration. Based on the factor analysis, five underlying factors were identified, comprising “team integration”, “collaborative tools and mechanisms”, “leadership and partners involvement”, “systematic process” and “training and motivation”. In sum, the findings of current study are likely to benefit the overall construction industry, allow industry practitioners to gain deeper insight of the potential hurdles to collaboration and support them with effective strategies for cultivating a collaborative working environment.